2002
DOI: 10.1007/s00204-002-0420-0
|View full text |Cite
|
Sign up to set email alerts
|

The anti-breast cancer drug tamoxifen alters Ca2+ movement in Chinese hamster ovary (CHO-K1) cells

Abstract: The anti-breast cancer drug tamoxifen has recently been shown to cause an increase in intracellular free-Ca(2+) concentrations ([Ca(2+)](i)) in renal tubular cells, breast cells and bladder cells. Because tamoxifen is known to alter ovary function in human patients and in rats, the present study was aimed at exploring whether tamoxifen could alter Ca(2+) movement in Chinese hamster ovary (CHO-K1) cells. Cytosolic free-Ca(2+) levels in populations of cells have been explored by using fura-2 as a fluorescent Ca(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…This infers that SERMs interact with the TG1 binding site. Indeed, it has been reported that pre‐treatment with a SERM (Tamoxifen ‐ TAM) inhibits the effect of TG1, increasing the intracellular Ca2 + concentration . We then performed further analysis by superimposing the AIT binding site (ERα) and the TG1 binding site (SERCA).…”
Section: Resultsmentioning
confidence: 75%
“…This infers that SERMs interact with the TG1 binding site. Indeed, it has been reported that pre‐treatment with a SERM (Tamoxifen ‐ TAM) inhibits the effect of TG1, increasing the intracellular Ca2 + concentration . We then performed further analysis by superimposing the AIT binding site (ERα) and the TG1 binding site (SERCA).…”
Section: Resultsmentioning
confidence: 75%
“…Because, in nondepolarizing cells, the majority of the basal calcium influx occurs through SOCC, the possible effect of tamoxifen on native TRPV6 activity was masked. Tamoxifen also exerts the same effect on SOCC activity in several cell types such as human oral cancer cells, CHO-K1 cells, human osteosarcoma cells, and ZR-75-1 human breast cancer cells (34)(35)(36)(37). This effect was shown not to be mediated by ERs.…”
Section: Discussionmentioning
confidence: 82%
“…SERMs, including 4-OHT, regulate microRNA expression in other cell lines but no one has evaluated their effects in CHO-K1 cells (Jan et al, 2003). Here, we report that 4-OHT increases miR-29b-1 and miR-29a expression in CHO-K1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…TAM concentrations greater than 5 μM were reported to decrease viability of CHO-K1 cells (Jan et al, 2003). Here we showed that 100 nM and 1 μM 4-OHT treatment did not have any significant effect on the viability, migration, invasion, or colony forming ability of CHO-K1 cells-even when miR-29b-1 or miR-29a were overexpressed or their activity repressed by anti-miR transfection.…”
Section: Discussionmentioning
confidence: 99%